Intellectual and developmental disabilities and Ontario's forensic inpatient system: a population-based cohort study. Issue 9 (21st October 2017) - Lin, Elizabeth; Barbaree, Howard; Selick, Avra; Ham, Elke; Wilton, Andrew S.; Lunsky, Yona
ABSTRACT: Individuals with intellectual and developmental disabilities (IDD) in forensic inpatient beds are both complex and understudied. Previous studies have been limited and largely based on smaller clinical samples. We used data from a population-based cohort of Ontario adults with IDD (H-CARDD cohort, n  = 66, 000) to describe their prevalence in forensic inpatient beds during 2005–2015 and compare their demographic and clinical profiles with non-IDD forensic patients. Results show that forensic patients with IDD and without IDD have similar profiles, with the exception that patients with IDD are more likely to have a psychiatric disorder and to be younger, rural, and have high or very high morbidity. Strong support was found for disproportionate admission: individuals with IDD are 12.2% of forensic inpatients but only 0.8% of the general population ( d  = 1.57). Support for disproportionate utilization was less dramatic and mixed. Little difference was found in terms of the per cent of longer-stay (treatment) admissions or multiple forensic admissions; however, patients with IDD did have longer number of bed days over 10 years (averaging 220.6 days more, d  = 0.28). A better understanding of the barriers to discharge for individuals with IDD will support implementation of appropriate pathways out of the hospital.